Bridging the Gap between Traditional Employment and Flexible Work: Opportunities and Challenges in Pakistan's Gig Economy - Dr. Maimoona Saleem; Naveed Farooq; Sajid Ali; Dr. Azhar Khan, (Dialogue Social Science Review (DSSR), 2025)
The aim of this study is to investigate the gig economy in Pakistan as a potential avenue for employment flexibility considering the sorrel state of unemployment and a weak economy. The gig economy has real value to those who are out chasing income opportunities, as it puts them onto the digital platform to various short-term jobs. Flexibility, the beautiful word that one uses to describe it, is accompanied by many challenges, such as insecurity about jobs, no social security benefits, and lots of grey areas in regulations. This, in turn, puts the gig workers in a vulnerable situation. The focus of the research fits within the framework of Labor Market Flexibility Theory so as to study the functioning of the gig economy in the unique socio-economic context of Pakistan. A review of the literature synthesizes existing research on gig work and emphasizes the need for all-encompassing regulations that not only protect workers but also provide some space for economic dynamism. The main findings from the current literature that although the gig economy is more supportive of economic resilience in providing a variety of employment, there are some worries when it comes to worker rights protection. The study mentioned several crucial challenges faced by gig workers, such as irregular incomes, loss of benefits normally associated with employment, and a formal operational character. These issues are, however, even more dramatic in the case of Pakistan, where proper jobs are limited, and many individuals have no option but to work on a gig basis to earn a living. On the framework of suggested solutions for these problems, this study recommends setting up a full-blown regulatory framework that will define workers' rights, a system for providing portable benefits for their essential protections, and skill development programs that would enhance workers' employability. Another extremely important area for concerted action would be the development of collaborative arrangements between gig platforms, emerged agencies, civil society organization, etc., to bring into being an ecosystem in support of gig workers. The implications of this research reach beyond the immediate terrain of Pakistan and illustrate wider themes of development, labor rights, and social equity in the gig economy. By applying measures to ensure that workers in the gig economy are protected while enabling all stakeholders to capitalize on that potential to help economic resilience, this study serves as an initial exposé on the characteristically Pakistani gig economy, setting the stage for additional research into this important area of labor market dynamics.